Applied materials engineering for orthodontic wires - Wilcock Arthur J. (Sciendo, 1989)
In Australia, the history of materials engineering for orthodontic wires is generally related to the development of the Begg appliance. Therefore, until recently, it has helped in the search for light resilient forces produced by fine high-tensile stainless steel wires. Recently there has been added the desire to include wires of a low modulus of elasticity which also produce light forces but in larger diameter rectangular wires. There have been three periods of development, namely, up to and including the Second World War, up to Dr Begg's passing, and subsequently.